Sarcopenia and cachexia: molecular mechanisms and therapeutic interventions - Tiantian Wang; Dong Zhou; Zhen Hong (MedComm)
Abstract Sarcopenia is defined as a muscle‐wasting syndrome that occurs with accelerated aging, while cachexia is a severe wasting syndrome associated with conditions such as cancer and immunodeficiency disorders, which cannot be fully addressed through conventional nutritional supplementation. Sarcopenia can be considered a component of cachexia, with the bidirectional interplay between adipose tissue and skeletal muscle potentially serving as a molecular mechanism for both conditions. However, the underlying mechanisms differ. Recognizing the interplay and distinctions between these disorders is essential for advancing both basic and translational research in this area, enhancing diagnostic accuracy and ultimately achieving effective therapeutic solutions for affected patients. This review discusses the muscle microenvironment's changes contributing to these conditions, recent therapeutic approaches like lifestyle modifications, small molecules, and nutritional interventions, and emerging strategies such as gene editing, stem cell therapy, and gut microbiome modulation. We also address the challenges and opportunities of multimodal interventions, aiming to provide insights into the pathogenesis and molecular mechanisms of sarcopenia and cachexia, ultimately aiding in innovative strategy development and improved treatments.